TRATEGIES FOR MANAGEMENT OF INTEGRATED PRODUCTION CHAINS UNDER THE CONDITIONS OF IMPLEMENTATION OF DIGITAL INNOVATIONS - MATIUKH, Serhii; SKOROBOGATA, Larysa; MISHCHUK, Maxim (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the scientific development of the theory of networks and flows from the standpoint of using their methodological approaches to solve the problems of forming a strategy for managing the innovative potential of cluster associations and finding new ways of its practical implementation. Strategic directions of business clustering under the condition of its digitization should ensure legislative support, appropriate digital infrastructure, elimination of digital gaps compared to other sectors of the economy, creation of proper conditions for the use of network tools, digital security, availability of regulatory support for innovation and investment development of network structures. This approach made it possible to form a set of principles and a portfolio of technologies for the interaction of network and integration structures, as well as to develop a digital mode of socio-economic transformations of integration production networks as components of ensuring sustainable competitive advantages under the conditions of globalization challenges. Fundamental aspects include: creation of a digital environment in which interaction between participants takes place with the help of digital services; formation of a secure digital asset management system; moving from descriptive to predictive and then administrative analytics. Based on these principles, a set of methodological tools for strategic management of the potential of network associations was developed and the main stimulators of investment and innovation development of integration production chains were established; a scientific hypothesis was formed, according to which digital management of latent manifestations of positive cluster properties should become the basis for the sustainable development of business associations.